Greenvec Game for Skin Conductivity Level (SCL) Biofeedback Performance Simulator Using Galvanic Skin Response (GSR) Sensor - Noraziah, Ahmad; Muhd Azrulnizam, Suna Abdullaha; Nurzety Aqtar, Ahmad Azuan; Mohammed Adam, Ibrahim Fakharaldien; Muhammad Nubli, Abdul Wahab (UMP Publisher, 2015)
The increasing fame of biofeedback game has brought convenience to human life. More and more people rely on biofeedback game as an alternative medical treatment to overcome their stress problems. GreenVec Biofeedback Game (GVBG) is a biofeedback game-based application that able to measure the skin conductivity of the player with an integration of Galvanic Skin Response (GSR) sensor. The measurement of the skin conductivity is crucial as an indicator for human meditation improvement in terms of stress control. In addition, GVBG spread awareness on global green technology issues, specifically about the Electric Vehicles (EV) topics to all users throughout the game process. The measured Skin Conductivity Level (SCL) corresponds to the player’s awareness of the green EV through the GVBG Simulator. Furthermore, GVBGsimulates the biofeedback performance through the measured SCL. It creates a short report on the player’s SCL based on the GSR sensor data and the game results at the end of the game session. From the results, the awareness on the EV is high when the SCL is high, whereas the awareness on the EV is low when the SCL is low. Therefore, GVBG Simulator helps users to train accordingly in order to reduce stress while at the same time gain awareness on the green technology issues with EV.